Uterine perforation following abortion in Tikur Anbessa Hospital, Addis Ababa, Ethiopia: A case series study - Tekle, Habtemariam; Kumbi, Solomon (Ethiopian Journal of Reproductive Health, 2018)
Abstract Objective: determine incidence, describe patient characteristics, examine clinical presentation, associated complications and describe mode of management of cases with uterine perforation. Methods: Operation registry, abortion care logbook and patients’ clinical records were reviewed in a teaching hospital in Addis Ababa, Ethiopia, between January 1, 1999 and December 31, 2000. Cases with laparatomy proven uterine perforation are described. Setting: obstetric and gynecologic department of a tertiary referral and teaching hospital in Addis Ababa, Ethiopia. Outcome measures: clinical presentation, intraoperative findings, site of perforation, mode of management, associated complications and outcome of treatment. Results: there were a total of 927 abortions of which 25 were laparatomy proven cases of uterine perforation following unsafe abortion, making the prevalence 27/1000 abortions. Majority were fond to be single, nulliparous, young and dependent member of the family. In 36% (9/25) termination was attempted after 14 weeks of gestation. Plastic and metallic materials are used frequently. Eight of the cases came after seven days of interference. The main clinical presentations were: abdominal pain (100%), signs of peritonitis (100%), pallor (96%), fever (76%) and vaginal bleeding (76%). Common intraoperative findings include abdominal abscess, adhesions, and inflamed ovaries and tubes. Frequent areas of perforation are posterior aspect of the body and cervico-isthmic region of the uterus. Drainage and lavage of the abdominal cavity (80%), hysterectomy (76%) and removal of adnexa (60%) were mainstays of management. All cases had sepsis and peritonitis, 24 had anemia, nine suffered from adult respiratory distress syndrome and eight developed wound infection. Duration of hospital stay ranged from one to 45 days. The case fatality rate was 32% (8/25). Only six came back for follow up. Conclusion: Uterine perforation is associated with increasing number of complications including death. Physicians catering the health care of women with unsafe abortion shall exhibit a high index of suspicion for uterine perforation. (Ethiop. J. Repro Health May 2007, 1(1):17-27)